Síntese de novas poliaminas naftoquinônicas derivadas da Lausona : aplicação como inibidor de corrosão e como potencial agente antineoplásico - Oliveira, Aldo Sena de (2010)
In this work we developed short and efficient synthetic routes for access to new polyamines naphthoquinone derivatives lawsone 60-90. To this end, initially was made a Mannich reaction between lawsone, benzoic aldehydes, 2-hydroxybenzoic and 2-hydroxy-1-naphthaldheyde and various primary and secondary amines and also with 2,4-dinitrophenylhydrazine to get the Mannich adducts 38-58 in good yields. Later, these adducts were subjected to a nucleophilic substitution reaction using as the nucleophiles ethylenediamine and 2-pycolilamine. The Mannich adducts were subjected to a study by cyclic voltammetry in aprotic and protic starting scanning -0.170 V, first vertex in V 1.5 and second vertex -2.0 V. The speeds chosen for the adducts were 10, 30, 50, 70, 100, 130, 150, 170 and 200 mV.s-1. The supporting electrolyte used was tetrabutylammonium perchlorate (TBAP). Then in the Mannich adducts 49, 52, 57 and 60-74 polyamines derived from ethylenediamine, 83, 85 and 89 derived from 2-pycolilamine were made the tests of inhibition corrosion using a three electrode electrochemical cell with the reference electrode Ag / AgCl, auxiliary electrode platinum electrodes and working steel AISI 1045, area of 1.327 cm2. The electrochemical measurements were performed in solutions containing 150 000 ppm of chloride ions and 5 ppm of sulfide ions. For each molecule was measured the open circuit potential, by 3600 / 2, to determine the corrosion potential (Ecorr) measures linear sweep of potential, ± 200 mV Ecorr, with a scan rate of 1 mV s-¹, to determine the corrosion rate in each medium. Measurements of electrochemical impedance spectroscopy (EIS) with a frequency of 10 kHz to 5 mHz and amplitude of 10 mV of the condition of stabilization of the electrodes, were performed to further characterize the system in stationary conditions. The equivalent circuit parameters were obtained by fitting with the Autolab FRA software. All polyamines tested, except 74 and 83, showed higher corrosion inhibition than tested commercial corrosion inhibitors (DSS, ETA and TEA). All synthesized compounds were evaluated for antineoplastic tests, using the MTT mitochondrial viability in ovarian cancer cells and human leukemia.